2016
DOI: 10.1111/bpa.12424
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 pathology in Alzheimer's disease, dementia with Lewy bodies and ageing

Abstract: Intracellular inclusions consisting of TAR DNA binding protein-43 (TDP-43 pathology) are present in up to 57% of Alzheimer's disease (AD) cases and follow a distinct topographical pattern of progression described in the TDP-43 in AD staging scheme. This scheme has not been applied to the assessment of TDP-43 pathology in dementia with Lewy bodies (DLB) and aged controls. We investigated TDP-43 pathology prevalence and severity in AD, DLB, mixed AD/DLB (Mx AD/DLB) and aged controls. One hundred and nineteen hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 187 publications
(205 citation statements)
references
References 39 publications
13
185
0
1
Order By: Relevance
“…Recently, Josephs and colleagues reported that TDP-43 pathology in AD is seen in over 50% of cases where it spreads in a distinct pattern [70, 71], which was also observed in LBD and aged controls by others [95]. Moreover, colocalization of phosphorylated TDP-43 and τ-containing NFTs has been reported but it is not yet clear whether this finding is due to unspecific co-staining of NFTs with the pTDP-43 antibody or whether indeed phosphorylated TDP-43 accumulates in NFTs.…”
Section: The Frontotemporal Lobar Degeneration: Amyotrophic Lateral Smentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, Josephs and colleagues reported that TDP-43 pathology in AD is seen in over 50% of cases where it spreads in a distinct pattern [70, 71], which was also observed in LBD and aged controls by others [95]. Moreover, colocalization of phosphorylated TDP-43 and τ-containing NFTs has been reported but it is not yet clear whether this finding is due to unspecific co-staining of NFTs with the pTDP-43 antibody or whether indeed phosphorylated TDP-43 accumulates in NFTs.…”
Section: The Frontotemporal Lobar Degeneration: Amyotrophic Lateral Smentioning
confidence: 95%
“…Respective data from neuropathological post-mortem studies are corroborated by in vivo imaging studies showing higher amyloid and τ levels in LBD compared to controls [46, 47]. While AD pathology is the most important co-morbidity in LBD cases, they may also show other pathologies such as cerebrovascular disease to varying degrees of severity in up to 75% [67] and TDP-43 pathology in over 30% of cases [95]. More quantitative data on the amount of pathological burden in large clinico-pathological cohorts are needed to clarify the relative influence of Aβ, τ, α-syn, and TDP-43 on the clinical picture.…”
Section: Overlap Of α-Syn With Other Pathologiesmentioning
confidence: 97%
See 2 more Smart Citations
“…We know that mixed neurodegenerative pathology is present in many if not most dementia patients, as evidence of α-synuclein, TDP-43, and vascular disesae are often observed alongside the typical Aβ plaques and tau neurofibrillary tangles[6668]. The potential contributions of these other pathologies to circadian dysfunction are unknown.…”
Section: What Do We Know About Circadian Dysfunction In Early or Presmentioning
confidence: 99%